Electrocardiographic recording (ECG) of hatchling females and males of scorpion mud turtle (Kinosternon scorpioides) subjected to restraint stress - Brenda Stefany dos Santos Braga; Deise de Lima Cardoso; Daniella Bastos de Araújo; Clarissa Araújo da Paz; Luciana Eiró-Quirino; Thaysa de Sousa Reis; Gabriela Brito Barbosa; Luana Vasconcelos de Souza; Laís Helena Baptista Amóras; Lucas Lima da Rocha; Maria Klara Otake Hamoy; José Ribamar Felipe Marques; et al. (Discover Animals)
Abstract The species Kinosternon scorpioides (scorpion mud turtle) has potential for commercial farming in captivity. Restraint is a stressful factor that can cause fatal reactions. However, research on stress in Muçuãs is scarce. Therefore, electrocardiography (ECG) is relevant because it allows precise diagnoses of cardiac events. The results revealed an increase in heart rate and amplitude in both sexes, with higher heart rates in males and greater amplitude in females. The P-Q interval decreased in females and remained unchanged in males. The QRS interval did not show statistically significant differences, but there was a slight decrease in males. The Q-T interval decreased in females, while it did not show significant variations in males. These findings suggest that the variation in intervals and, consequently, heart rate occurs due to the regulation of the adrenergic pathway during periods of stress in turtles, mainly due to high concentrations of β-adrenergic receptors. Therefore, it was shown that both females and males experienced cardiovascular instability during restraint stress, with greater instability in males.